“Mari kitorang bapesta”: Budaya Pesta Dalam Masyarakat Minahasa Dilihat Dari Kacamata Hirarki Kebutuhan Maslow Dan Collective Self-Esteem - Subekti, Helen; Yuwanto, Listyo (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Minahasan people of North of Sulawesi, Indonesia have a unique culture surrounding the feast. This culture can be traced as far as centuries old and was referring to the act of prayers and gratitude toward Gods and the ancestors for the overflowing harvest. As the time goes by, gratitude is no longer the sole reason for why this feast is being held. The feast has become a statement of social identity among the Minahasan. This also caused social problems such as debt-culture; taking debts from friends, family and/or neighbors for those who cannot afford to hold the feast then another problem arises when they cannot afford to pay their debts back. It has happened way too often that it caused plenty of conflicts between families, friends and/or neighbors. Through this paper, it has been found that multiple needs such as physiological, love and sense of belonging and esteem are fulfilled thoroughly. The esteem needs that are fulfilled can also relate to the collective self-esteem that can be seen through the solidarity of each member of the society supporting the feast to be held.